Introdução ao infinitismo na epistemologia : uma resposta ao Trilema de Agripa - Cibils, Samuel Vicente Basso (2023)
Skepticism in epistemology refers to the supposedly irrational attitude of suspending judgment about all beliefs, particularly those taken for granted. The skeptical attitude presses philosophy to investigate the conditions under which knowledge and justification rather than accidental truths can be arrived at. In the first chapter, we will investigate how to construct a form of radical skepticism known as Pyrrhonian skepticism; we will see how Agrippa's Trilemma builds three ways of skeptical defense to object to three possible conditions in the structuring of epistemic justification. In the second chapter, we will examine infinitism as a possible answer to the trilemma, as well as the conceptual bases that make possible the existence of this possible solution to the skeptical challenge. In the third, the main objection to infinitism known as the finite mind problem will be analyzed. In the fourth chapter, we will look at an alternative formulation of the trilemma, as well as the challenges this approach poses to the anti-skeptical response